Implementation of the Problem-Based Learning Model in Social Studies Subjects in Class VIII of SMP 27 Samarinda - Nabilah Nabilah; Aulia Rahuma (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2025)
The purpose of this study was to determine how the implementation of the problem based-learning model in social studies learning in class VIII of SMP Negeri 27 Samarinda. The focus of this study is how the implementation of problem based-learning and the obstacles experienced in implementing the problem based-learning learning model in social studies learning. The research method used is a qualitative approach with a case study research type. The data collection techniques used by the researcher are observation, interviews with teachers and students and documentation. The results of the study showed that the implementation of the problem based-learning model in social studies learning in SMP Negeri 27 Samarinda went quite well. At the preparation stage, teachers prepared teaching modules, media and learning resources. The learning media used in problem based-learning learning were whiteboards and videos downloaded from the internet. The implementation of problem based-learning in SMP Negeri 27 Samarinda has several stages starting from opening learning and ending with learning evaluation. Evaluation of problem based-learning learning is an important aspect that aims to measure the effectiveness and impact of this learning model on student development. However, there are also obstacles faced by teachers such as lack of IT, mastery by both teachers and students, time constraints, student characteristics, and management of group dynamics.